Penerapan Euclidean Distance untuk analisis driver variable Perubahan Penggunaan Lahan dari Jarak Jalan di Sub-DAS Cikapundung - A. Leonardo, Patrick; Arifin, Mahfud; Siswanto, Shantosa Yudha (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
The Cikapundung Sub-watershed is part of the Upper Citarum Watershed, with its catchment area covering West Bandung Regency, Bandung City, and Bandung Regency. The increasing land use activities in the Cikapundung Sub-watershed have driven significant development activities in the upper areas of the subwatershed. One of the factors influencing this development is the road network, which affects the accessibility of an area, known as the driver variable. The creation of this driver variable requires GIS analysis using the Euclidean distance module, which calculates the distance from the roads. This calculation yields radial distances, ranging from the farthest to the nearest distances. It is known that local roads are the longest in the Cikapundung Sub-watershed, reaching 644.31 km. Based on the Euclidean distance calculation, the farthest distance from the road is 9504.22 meters, and the nearest is 0 meters. The map resulting from this calculation can be used to analyze the extent to which the distance from the road influences land use changes as a driver variable in the Cikapundung Sub-watershed.